2008
DOI: 10.1128/jvi.02388-07
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of the Human Papillomavirus Type 16 E2 N Terminus Results in DNA Looping within the Upstream Regulatory Region

Abstract: Papillomavirus E2 proteins play a central role in regulating viral gene expression and replication. DNAbinding activity is associated with the C-terminal domain of E2, which forms a stable dimer, while the N-terminal domain is responsible for E2's replication and transactivation functions. The crystal structure of the latter domain revealed a second dimerization interface on E2 which may be responsible for DNA loop formation in the regulatory region of the human papillomavirus (HPV) genome. We investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
(48 reference statements)
1
11
1
Order By: Relevance
“…For E2 from human papillomavirus type 16 (HPV16), dimerization of the TAD was found to involve two of the three α-helices that form part of the Brd4-binding surface (Antson et al, 2000). This TAD–TAD interface was shown to occur between different E2 dimers as it can promote DNA-looping between E2 dimers bound at distant sites in vitro (Antson et al, 2000; Hernandez-Ramon et al, 2008). A very different TAD dimerization interface was identified for BPV1 E2.…”
Section: Introductionmentioning
confidence: 99%
“…For E2 from human papillomavirus type 16 (HPV16), dimerization of the TAD was found to involve two of the three α-helices that form part of the Brd4-binding surface (Antson et al, 2000). This TAD–TAD interface was shown to occur between different E2 dimers as it can promote DNA-looping between E2 dimers bound at distant sites in vitro (Antson et al, 2000; Hernandez-Ramon et al, 2008). A very different TAD dimerization interface was identified for BPV1 E2.…”
Section: Introductionmentioning
confidence: 99%
“…The E2 transactivation domain has also been implicated in self-interaction, and the looping of DNA containing E2 binding sites has been observed previously by electron microscopy for BPV-1, human papillomavirus type 16 (HPV-16), and HPV-11 E2 proteins (3,11,15,29). For HPV-16 E2, selfinteraction involves residues R37 and I73, which are also crucial for Brd4 binding (1,5,20), and thus, self-interaction may modulate Brd4 binding.…”
Section: Discussionmentioning
confidence: 99%
“…Such structure will result in the tissue-specific enhancers shifting closer to the core transcription complex for transcriptional activation [20,21]. Meanwhile, some studies have indicated that binding of the intact E2 to the LCR sequences may spatially prevent the transcriptional machine to active the promoter, which are the main molecular mechanism for E2 transcriptional repression [22,23].…”
Section: Discussionmentioning
confidence: 99%